MANAJEMEN RETENSI URIN PADA LANSIA DI IGD: STUDI KASUS DARI RS PKU MUHAMMADIYAH GAMPING - Meisty, Meisty Anggraeni; Efi Fibriyanti (Sekolah Tinggi Ilmu Kesehatan Katolik St. Vincentius a Paulo Surabaya, 2025)
Urinary Retention is a condition of inability to urinate even though the bladder is full and this condition is often accompanied by a sensation of pain. Urinary retention is an inability to empty the bladder until the bladder capacity is exceeded. According to research, over the past 5 years, 10% of men over the age of 70 and a third of men in their 80s have experienced acute urinary retention. The death rate that soared in 1 year at the age of 45-54 years was 4.1% while those aged 85 years and over became 33%. Acute urinary retention most often occurs in men aged 60 to 80. Several studies have shown that over five years, 10% of men over the age of 70 and almost a third of men in their 80s will experience acute urinary retention. Nursing diagnosis analysis In patient Mrs. P, nursing was obtained, namely urinary retention, risk of fluid imbalance, and acute pain. The priority diagnosis taken was urinary retention. The author has a goal in SLKI, namely Urine Elimination (L.04034). SIKI Urine Catheterization is inserting a urine catheter tube into the bladder. Nursing evaluation in the case of Mrs. P after nursing actions for 1X4 hours, the problem of urinary retention nursing related to increased urethral pressure has not been resolved. Based on the results of data analysis, it can be concluded that the actions given are in accordance with the diagnosis but the problem of urinary retention has not been resolved